Health care utilization and steroid‐refractory toxicities from immune checkpoint inhibitors. Issue 2 (3rd October 2019) - Wang, Laura X.; Quach, Henry T.; Moodabigil, Nikil V.; Davis, Elizabeth J.; Sosman, Jeffrey A.; Dusetzina, Stacie B.; Johnson, Douglas B.
Abstract : Background: Anti–programmed death protein 1 (anti–PD‐1) agents have transformed the treatment of advanced melanoma and other cancers, but the rates of steroid‐refractory toxicities and health care utilization are not well described. This study assessed these endpoints in patients with melanoma treated with anti–PD‐1 with or without ipilimumab. Methods: This study retrospectively evaluated 344 patients with metastatic melanoma treated with anti–PD‐1 or a combination of ipilimumab and nivolumab at Vanderbilt University Medical Center from 2009 to 2018. The incidence, types, grades, management, and outcomes of immune‐related adverse events (irAEs) and hospitalizations for irAEs and disease progression were assessed. Results: Patients on combination therapy were more likely to develop irAEs than those on monotherapy (72% vs 37%; P  < .001) and were more likely to require systemic steroids (61% vs 20%; P  < .001), steroid dose re‐escalation (23% vs 6%; P  < .001), and second‐line immunosuppressive use (17% vs 2%; P  < .001) and to suffer high‐dose steroid–refractory toxicities (23% vs 3%; P  < .001). Combination‐treated patients were more likely to have any hospitalization (32% vs 7%; P  < .001) or multiple hospitalizations for irAEs (11% vs 3%; P  = .001) and had a longer average time of hospitalization (mean, 1.92 vs 0.62 days; P  = .002). Among 176 hospitalizations related to disease progression in patients who died during evaluable follow‐up, 69% occurred within the 90 days before death. Early hospitalizations for disease‐related reasons portended a very poor prognosis (median time from admission to death, 58 days). Conclusions: Patients treated with a combination of ipilimumab and nivolumab had higher rates of hospitalization and steroid‐refractory toxicities than those treated with anti–PD‐1 monotherapy. Disease‐associated hospitalizations were similar between the 2 groups, portended a poor prognosis, and mostly occurred in the last months of life. Abstract : Immune checkpoint inhibitors cause immune‐related toxicities; the rates of steroid‐refractory events, the need for additional immunosuppression, and hospitalizations are not well described. This study shows that a combination of immune checkpoint inhibitors is linked with higher rates of steroid‐refractory toxicities and health care utilization in comparison with monotherapy; hospitalizations for disease are clustered at the end of life.